Anti-Chikungunya Virus Monoclonal Antibody That Inhibits Viral Fusion and Release - Tumkosit, Uranan (J Virol, 2020)
Chikungunya fever, a mosquito-borne disease manifested by fever, rash, myalgia, and arthralgia, is caused by chikungunya virus (CHIKV), which belongs to the genus Alphavirus of the family Togaviridae. Anti-CHIKV IgG from convalescent patients is known to directly neutralize CHIKV, and the state of immunity lasts throughout life. Here, we examined the epitope of a neutralizing mouse monoclonal antibody against CHIKV, CHE19, which inhibits viral fusion and release. In silico docking analysis showed that the epitope of CHE19 was localized in the viral E2 envelope and consisted of two separate segments, an N-linker and a β-ribbon connector, and that its bound Fab fragment on E2 overlapped the position that the E3 glycoprotein originally occupied. We showed that CHIKV-E2 is lost during the viral internalization and that CHE19 inhibits the elimination of CHIKV-E2. These findings suggested that CHE19 stabilizes the E2-E1 heterodimer instead of E3 and inhibits the protrusion of the E1 fusion loop and subsequent membrane fusion. In addition, the antigen-bound Fab fragment configuration showed that CHE19 connects to the CHIKV spikes existing on the two individual virions, leading us to conclude that the CHE19-CHIKV complex was responsible for the large virus aggregations. In our subsequent filtration experiments, large viral aggregations by CHE19 were trapped by a 0.45-μm filter. This virion-connecting characteristic of CHE19 could explain the inhibition of viral release from infected cells by the tethering effect of the virion itself. These findings provide clues toward the development of effective prophylactic and therapeutic monoclonal antibodies against the Alphavirus infection. IMPORTANCE Recent outbreaks of chikungunya fever have increased its clinical importance. Neither a specific antiviral drug nor a commercial vaccine for CHIKV infection are available. Here, we show a detailed model of the docking between the envelope glycoprotein of CHIKV and our unique anti-CHIKV-neutralizing monoclonal antibody (CHE19), which inhibits CHIKV membrane fusion and virion release from CHIKV-infected cells. Homology modeling of the neutralizing antibody CHE19 and protein-protein docking analysis of the CHIKV envelope glycoprotein and CHE19 suggested that CHE19 inhibits the viral membrane fusion by stabilizing the E2-E1 heterodimer and inhibits virion release by facilitating the formation of virus aggregation due to the connecting virions, and these predictions were confirmed by experiments. Sequence information of CHE19 and the CHIKV envelope glycoprotein and their docking model will contribute to future development of an effective prophylactic and therapeutic agent.